Acute adjustments of heart rate and oxygen consuption in an experimental protocol of step training with diferent combinations of platform height and musical rhythms - doi: 10.4025/actascihealthsci.v35i2.11669 (Acta Scientiarum. Health Sciences, 2013)
The aim of this study was to investigate adaptations acute heart rate (HR) and oxygen consumption (VO2) in an experimental protocol of step training with different combinations of platform height (15.2, 20.3 and 25.4 cm) and musical rhythms (125, 135 and 145 bpm). Thirty-five women were randomly selected, (mean ± DP) aged 21.6 ± 1.8 years, body weight of 57.8 ± 8.2 kg, height of 162.6 ± 6.8 cm, body mass index of 21.8 ± 2.5 kg m-2 and fat percentage (% Fat) of 24.8 ± 4.4%, with at least six months experience in step training sessions, and a frequency of at least two days a week. Techniques of descriptive and inferential statistics were employed. A significant difference was detected for the HR and VO2 in relation to the increase in step platform height and in musical rhythm for all the combinations, except for three situations. From the obtained results, we can infer that the cardiovascular and metabolic responses increase or decrease according to the musical rhythm and/or platform height.